1987
DOI: 10.1128/jvi.61.4.1061-1066.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of human fibroblasts and keratinocytes with human papillomavirus type 16 DNA

Abstract: Human keratinocytes and fibroblasts isolated from foreskin were transformed by transfection with recombinant human papillomavirus type 16 (HPV16) DNA. The transformed cells exhibited an extended (fibroblasts) or indefinite (keratinocytes) lifespan compared with that of normal controls. In addition, HS27, a human fibroblast cell line previously transfected with origin-defective simian virus 40, was successfully transfected. HPV16 sequences were stably maintained in the cells, and extensive amplification and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
133
0
4

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(140 citation statements)
references
References 26 publications
3
133
0
4
Order By: Relevance
“…DNA of HPV types 16 and 18 can transform or immortalize a variety of cell types in vitro, including primary human foreskin keratinocytes (Yasumoto et al, 1986Diirst et al, 1987b;Matlashewski et al, 1987;Pirisi et al, 1987;McCance et al, 1988;Schlegel et al, 1988;. This activity has been mapped to the E6 and E7 viral genes (Bedell et al, 1989;Hawley-Nelson et al, 1989;Watanabe et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…DNA of HPV types 16 and 18 can transform or immortalize a variety of cell types in vitro, including primary human foreskin keratinocytes (Yasumoto et al, 1986Diirst et al, 1987b;Matlashewski et al, 1987;Pirisi et al, 1987;McCance et al, 1988;Schlegel et al, 1988;. This activity has been mapped to the E6 and E7 viral genes (Bedell et al, 1989;Hawley-Nelson et al, 1989;Watanabe et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Cell lines derived from cervical cancers such as HeLa, CaSki and SiHa cells, have been shown to contain and express HPV DNA (121)(122)(123). Experimental studies have demonstrated that some HPV's are capable of transforming rodent cells and immortalizing human foreskin (124,125), and cervical keratinocytes (126,127). Recently, MCCANCE et al (128) and WOOD WORTH et al (126) demonstrated that HPV 16 and HPV 18 induced morphologic abnormalities in vitro on human keratinocytes closely resembling those of dysplastic cells.…”
Section: Human Papillomavirusesmentioning
confidence: 99%
“…A substantial amount of evidence is available to suggest that specific genotypes of HPV are necessary but insufficient in malignant transformation, synergistic actions with other initiating events being evidently required (122,123). This speculation is based on the following facts: (a) the repeated application of methylcholanthrene or tar to cottontail rabbit papillomavirus (CRPV)-induced papillomas in domestic rabbits markedly enhanced their malignant transformation (129); (b) bovine papillo-mavirus (BPV)-induced alimentary tract (esophageal) papillomas in cattle showed an increased tendency to malignant transformation in animals feeding on the bracken fern which contains potent carcinogens (130,131); (c) many cases of juvenile laryngeal papillomas converted into squamous cell carcinomas after therapeutic X-ray irradiation with a latency period of 5-40 yr (132); (d) about 30% of EV patients developed skin cancers on an average of 24 yr after the onset of the disease, mainly at sun-exposed sites (133); (e) specific types of HPVs can induce immortalization in cultured human foreskin and cervical epithelial cells but the immortal cells are not tumorigenic in athymic mice (124,126,127), indicating that additional factors are necessary for the final malignant conversion.…”
Section: Human Papillomavirusesmentioning
confidence: 99%
“…In this type of experiment, cell lines are usually manipulated by either drug treatment, ectopic gene expression or knock down and subsequently interrogated at regular intervals over time. One well-known example for this is the study of cellular immortalization and transformation by (viral) oncogenes, including the human papillomavirus (HPV)-encoded E6 and E7 (Band, Zajchowski, Kulesa, & Sager, 1990;Dürst et al, 1987;Park et al, 1991;Pecoraro, Morgan, & Defendi, 1989;Pirisi et al, 1987;Willey et al, 1991). The resulting sequential snapshots of the activity of each molecular entity provide insight into the dynamic aspects of the regulatory system.…”
Section: Introductionmentioning
confidence: 99%